Decomposition and Conceptualization to Support System Dynamics Behavior Modeling - Fiona Tulinayo; Theo van der Weide; Patrick van Bommel (Complex Systems Informatics and Modeling Quarterly)
With the increasing need for data-based decision making, social systems and the ecosystems; practitioners and decision makers need guidance in their decision making, as is offered by data-based models and a systematic generation of simulation tools. Overtly, relations between data and practice have been under-conceptualized. Data modelers and decision makers tend to lack a mutual understanding of each other’s knowledge systems which has led to huge knowledge gaps. Assimilation of modeling methods therefore is vital. Modeling methods use a specific way of thinking, rules and directions on how to model different aspects of systems. These rules and directions are what we refer to as constructs. Conceptualizing model relations and formulations requires significant domain knowledge and understanding of the constructs. In this article, we use the decomposition mechanism to better conceptualize and understand the System Dynamics (SD) model behavior, and show how using a natural language based domain modeling method (Object-Role Modeling, ORM) helps in dealing with complex SD models. Through applying the decomposition mechanism, we are able to better understand the underlying concepts of the stock and flow diagram and update behaviors of ORM objects. To achieve this, we use examples and an SD model derived from a case “Intrapartum process in Ugandan hospitals” to study the object behaviors. The main results of this article include: a theoretical founding of integrating ORM with SD; quantitative analysis at the level of ORM reasoning; and transformation rules from ORM into SD.